2022
DOI: 10.3389/fpls.2022.772054
|View full text |Cite
|
Sign up to set email alerts
|

Widening the Perspectives for Legume Consumption: The Case of Bioactive Non-nutrients

Abstract: Legume grains have provided essential nutrients in human diets for centuries, being excellent sources of proteins, carbohydrates, fatty acids, and fibers. They also contain several non-nutrients that historically have been connotated as toxic but that in recent years have been shown to have interesting bioactive properties. The discussion on the role of bioactive non-nutrients is becoming more important due to increasing science-based evidence on their potential antioxidant, hypoglycemic, hypolipidemic, and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 98 publications
(124 reference statements)
1
32
0
1
Order By: Relevance
“…Data in 2011–2013 indicated that legumes were consumed the most in Latin America and the Caribbean (about 33–34 g per capita per day), followed by sub-Saharan Africa and South Asia, while those in Southeast Asia, including Thailand, consumed approximately 10 g of legumes per capita per day [ 8 ]. Beans have been recognized as food ingredients rich in protein, vitamins, minerals, and phytonutrients [ 9 ]. For example, the common bean ( Phaseolus vulgaris ) variety ‘American black’ cultivated in Mexico possesses protein, total dietary fiber, and lipids at 20.4, 23.4, and 3.6 g/100 g of dry sample, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Data in 2011–2013 indicated that legumes were consumed the most in Latin America and the Caribbean (about 33–34 g per capita per day), followed by sub-Saharan Africa and South Asia, while those in Southeast Asia, including Thailand, consumed approximately 10 g of legumes per capita per day [ 8 ]. Beans have been recognized as food ingredients rich in protein, vitamins, minerals, and phytonutrients [ 9 ]. For example, the common bean ( Phaseolus vulgaris ) variety ‘American black’ cultivated in Mexico possesses protein, total dietary fiber, and lipids at 20.4, 23.4, and 3.6 g/100 g of dry sample, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Heterocyclic compounds with diphenyl sulfone moiety exhibited a significant improvement in the antiviral and other defensive properties of HR [ 46 ]. The antimicrobial and antioxidant activities of papaveroline and 2,2-Dimethyl-5-[2-(2-trimethylsilyl ethoxy methoxy)-propyl]-[ 1 , 3 ]dioxolane-4-carboxaldehyde were documented by [ 47 , 48 ], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Legumes are an excellent rotational crop [ 1 ], and their cultivation enhances soil carbon levels, reduces the need for fossil fuel use in farming [ 2 ], reduces soil erosion, and improves soil fertility through symbiotic relationships [ 1 ]. The demand-driven changes in agriculture cultivation practices, such as intensification systems and unbalanced animal-food-based protein consumption, warrant the promotion of legume proteins [ 3 ]. Legumes adequately satisfy human protein requirements [ 4 ] and provide a balanced diet, as they possess a good quantity of fiber, carbohydrates, vitamins, and minerals [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oxalates, such as oxalic acid, are referred to as antinutritional factors causing hypocalcemia, mineral bioavailability disorders and stone disorders [ 79 , 80 , 81 ]. In our study, the advanced line KK14 had the highest concentration of oxalic acid, as well as other antinutritional factors such as total phenols and tannins [ 82 ]; thus, it is inappropriate for further use in breeding programs.…”
Section: Discussionmentioning
confidence: 99%